GENDER-BASED TAX COMPLIANCE IN THE DIGITAL ECOSYSTEM - Alistraja Dison Silalahi; Cita Ayni Putri Silalahi; Rukmini; Mohd. Idris Dalimunthe; M. Bayu Trianto; Narong Hassanee (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This study aims to find and analyze the influence of service quality and attitudes experienced by MSME taxpayers on tax compliance decision-making behavior, with intention as a mediator and tax literacy as a moderating variable. This study provides a detailed analysis of the problem studied and validation of the analysis of decision-making to comply with tax obligations, based on a survey of 216 MSMEs in North Sumatra. This study is a quantitative study with a causal nature. The data analysis technique uses statistical analysis based on partial least squares (PLS). The results of the study found that service quality, attitude, and financial literacy influence taxpayer intention and compliance; Intention influences tax compliance; Intention mediates the relationship between service quality, taxpayer attitude, and tax literacy on tax compliance; Tax literacy is unable to moderate the relationship between service quality, taxpayer attitude, and taxpayer intention.